Effect of Citric Acid Concentration on the Transformation of Aragonite CaCO3 to Calcium Citrate Using Cockle Shells as a Green Calcium Source - Pantita Chanwetprasat; Chaowared Seangarun; Somkiat Seesanong; Banjong Boonchom; Nongnuch Laohavisuti; Wimonmat Boonmee; Pesak Rungrojchaipon (My University, 2025)
Aragonite calcium carbonate (CaCO3), derived from cockle shell waste, was successfully used as a renewable calcium source to synthesize calcium citrate (CCT) using citric acid (C6H8O7). The three CCT products (CCT-2, CCT-3, and CCT-4) were prepared using three different acid concentrations: 2, 3, and 4 M. The physicochemical characteristics of the newly synthesized CCT were investigated. Fourier-transform infrared (FTIR) spectra revealed the vibrational modes of the citrate anionic group (C6H5O73-), which preliminarily confirmed the characteristics of CCT. However, X-ray diffraction (XRD) revealed that the concentration of citric acid altered the structural property and the chemical formula of the synthesized CCT. Employing 2 M citric acid, a pure tetra-hydrated phase (Ca3(C6H5O7)2·4H2O, earlandite mineral) was obtained. However, a mixture of hydrated (Ca3(C6H5O7)2·4H2O) and anhydrous (Ca3(C6H5O7)2) phases was precipitated when 3 and 4 M citric acid was used in the preparation process. The lower mass loss observed in the thermogravimetric analysis (TGA) of CCT-3 and CCT-4 compared to that of CCT-2 further confirmed that CCT-3 and CCT-4 were composed of hydrated and anhydrous CCTs. The synthesized CCT decomposed in four major processes: the first dehydration, the second dehydration, CaCO3 formation, and decarbonization, generating calcium oxide (CaO) as the final product. X-ray fluorescence (XRF) results showed that the CCT mainly consisted of CaO with a quantity of >98%. The scanning electron microscopic (SEM) image revealed the irregular plate-like CCT crystallites. The concentration of citric acid is a key factor that influences the productive parameters of CCT, including production yield, reaction time, and solubility. 2 M citric acid provided the optimal balance between productivity and cost-effectiveness, with the highest yield and soluble fraction and the lowest reaction time. The results suggest that the preparation of CCT from cockle shell waste can potentially replace the use of commercial calcite from mining, which is a limited and non-renewable resource.
Keywords: Cockle; Calcium Carbonate Crystallization and Inhibition